2018
DOI: 10.1097/pas.0000000000001161
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Subtypes of Lung Adenocarcinoma Brain Metastasis Is a Strong Predictor of Survival After Resection

Abstract: Primary lung adenocarcinoma is classified according to predominant histopathologic architecture into lepidic, papillary, acinar, solid, and micropapillary subtypes. These subtypes are related to overall survival in primary lung adenocarcinoma. The main goal of our work was to evaluate the prognostic impact of this classification on surgical resection of brain adenocarcinoma metastases in 97 patients with surgically resected brain metastases of lung adenocarcinoma from 2008 to 2017. Histopathologic subtype is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 19 publications
1
24
0
Order By: Relevance
“…In a previous study, we showed that even grading of lung adenocarcinoma Bmets has an important prognostic impact. 12 Furthermore, we found important correlations between the primary tumor's infiltration by CD8-positive lymphocytes and brain metastasis characteristics. Specifically, primary tumors less infiltrated by CD8 cells gave multiple BM most often, as well as metastases that reveal the primary tumor and occipital metastases.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In a previous study, we showed that even grading of lung adenocarcinoma Bmets has an important prognostic impact. 12 Furthermore, we found important correlations between the primary tumor's infiltration by CD8-positive lymphocytes and brain metastasis characteristics. Specifically, primary tumors less infiltrated by CD8 cells gave multiple BM most often, as well as metastases that reveal the primary tumor and occipital metastases.…”
Section: Discussionmentioning
confidence: 71%
“…Molecular analysis was performed for 93 cases (lung adenocarcinomas, melanomas, and gastrointestinal carcinomas), as previously described. [10][11][12] Briefly, formalinfixed paraffin-embedded tumor sections were used for DNA extraction (automated extraction: Qiacube kit used; Qiagen, Courtaboeuf, France). DNA concentration and quality were assessed by the Qubit method and a Nanodrop spectrophotometer (Thermo Fisher Scientific, Waltham, Massachusetts, USA).…”
Section: Molecular Analysismentioning
confidence: 99%
“…Adenocarcinoma may consist of some cubic tumor cells and some columnar [32]. The pathology of primary lung adenocarcinoma is mostly papillary type, others are solid, lepidic, acinar, and micropapillary subtypes., which is often diagnosed as a mixture of multiple subtypes [33]. The pathological subtypes of lung squamous cell carcinoma include small cell, clear cell, basaloid and papillary subtypes [6,34], in which papillary squamous cell carcinoma is usually characterized by exogenous endobronchial growth [35].…”
Section: Discussionmentioning
confidence: 99%
“…Adenocarcinoma may consist partly cubic tumor cells and partly of columnar [29]. The pathology of primary lung adenocarcinoma is mostly papillary type, others are solid, lepidic, acinar, and micropapillary subtypes., which is often diagnosed as a mixture of multiple subtypes [30]. The pathological subtypes of lung squamous cell carcinoma include small cell, clear cell, basaloid and papillary subtypes [6,31], in which papillary squamous cell carcinoma is usually characterized by exogenous endobronchial growth [32].…”
Section: Discussionmentioning
confidence: 99%